Analisis Resiko Kebangkrutan Pt Superkrane Mitra Utama Dengan Metode Z Score Dan Zmijewski Periode Tahun 2017-2019 - Putri, Syamsi Melati (BISMA : Business and Management Journal, 2023)
This analysis aims to predict the probability of bankruptcy of PT Superkrane Mitra Utama during the 2017-2019 season using the Altman Z-Score method. This research uses a descriptive approach with a quantitative method. The research sample is from PT Superkrean Mitra Utama, and the instrument used is the company's financial report. Data was collected through literature study, and data analysis was carried out using the t-theist onei sample technique. The research results show that based on analysis using the Altman Z-Score method, PT Superkrean Mitra Utama during the 2017-2019 period is projected not to have the potential to go bankrupt because of the average Z value ≥ 1.10. This indicates that the company is in a safe condition from the risk of bankruptcy to a healthy level